Acute effects of whole-body vibration on muscle activity, strength, and power - Cormie, P.; Deane, R. S.; Triplett, N. T.; McBride, J. M. (The Journal of Strength and Conditioning Research, 2006)
The purpose of this study was to investigate the effects of a single bout of whole-body vibration on isometric squat (IS) and countermovement jump (CMJ) performance. Nine moderately resistance-trained men were tested for peak force (PF) during the IS and jump height (JH) and peak power (PP) during the CMJ. Average integrated electromyography (IEMG) was measured from the vastus medialis, vastus lateralis, and biceps femoris muscles. Subjects performed the 2 treatment conditions, vibration or sham, in a randomized order. Subjects were tested for baseline performance variables in both the IS and CMJ, and were exposed to either a 30-second bout of whole-body vibration or sham intervention. Subjects were tested immediately following the vibration or sham treatment, as well as 5, 15, and 30 minutes posttreatment. Whole-body vibration resulted in a significantly higher (p 0.05) JH during the CMJ immediately following vibration, as compared with the sham condition. No significant differences were observed in CMJ PP; PF during IS or IEMG of the vastus medialis, vastus lateralis, or biceps femoris during the CMJ; or IS between vibration and sham treaments. Whole-body vibration may be a potential warm-up procedure for increasing vertical JH. Future research is warranted addressing the influence of various protocols of whole-body vibration (i.e., duration, amplitude, frequency) on athletic performance.